2012
DOI: 10.1097/jto.0b013e31823a39e8
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized Trial of Erlotinib or Vinorelbine in Chemonaive, Advanced, Non-small Cell Lung Cancer Patients Aged 70 Years or Older

Abstract: Erlotinib is highly effective compared with oral vinorelbine in elderly, chemonaive, Taiwanese patients with NSCLC. EGFR-mutated patients had better survival than those with EGFR wild-type disease, regardless of the treatment received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…Erlotinib was found to be superior to vinorelbine in terms of objective response rate and pfs, but the difference in os was not statically significant (median survival duration: 11.6 months vs. 9.3 months respectively) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Erlotinib was found to be superior to vinorelbine in terms of objective response rate and pfs, but the difference in os was not statically significant (median survival duration: 11.6 months vs. 9.3 months respectively) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the response rate favoured the egfr inhibitor 21 , and in four studies, it favoured chemotherapy 13,14,[19][20][21] . The study by Reck et al 19 found a significantly higher response rate in patients randomized to chemotherapy (p = 0.0001).…”
Section: First-line Treatmentmentioning
confidence: 99%
“…Median pfs was similar in two trials 14,18 . In one trial, pfs was longer in the egfr inhibitor group: 4.57 months for erlotinib versus 2.53 months for vinorelbine (hr: 0.6444; 95% ci: 0.4325 to 0.9601; p = 0.0308) 21 . In five trials, pfs was longer in the chemotherapy group 13,15,17,19,20 .…”
Section: First-line Treatmentmentioning
confidence: 99%
“…Although older and younger patients achieved comparable PFS, OS and RRs, older patients suffered worse toxicity due to rash, fatigue and dehydration [70] . Erlotinib performed better than vinorelbine in a subgroup of EGFR mutation positive elderly patients as shown in a prospective phase Ⅱ trial while failed to gain advantage when added to gemcitabine or compared to it in molecularly not selected elderly patients [71,72] .…”
Section: Egfr Tyrosine Kinase Inhibitorsmentioning
confidence: 99%